Social Communication Intervention via Telehealth Following Traumatic Brain Injury in Adults: A Systematic Review - Christie-Taylor, Taryn (Department of Psychology, 2023)
Introduction: Traumatic brain injury (TBI) is a leading cause of death and disability, affecting millions of individuals annually worldwide. Neuropsychological sequalae following TBI are multiple and heterogenous, with the combination of such deficits having a marked impact on individuals' ability to effectively communicate. Functional implications of impaired communicative competence are profound and long-lasting, therefore warranting intervention. Neurorehabilitation targeting social communication post-TBI has to date been dominated by social skills and communication partner training, with telehealth (TH) delivery thereof recently emerging as a promising avenue of intervention. Method: This systematic review of social communication intervention via TH following TBI, was structured according to PRISMA guidelines, involved searching six scientific databases and included four studies which were evaluated using Cicerone et al.'s (2009) and Tate et al.'s (2008) checklists for methodological quality. Results: In both a single-case experimental design and clinical trial of a TH intervention program, TBIconneCT, improvements in conversational skills and quality were recorded on independent observer and self-report measures. Results of participants receiving TH intervention appear comparable to that of in-person (IP) counterparts. Across studies the logistics of TH delivery did not seem to detract from the subjective experience of intervention with participants reporting high levels of acceptability, and feasibility. Conclusion: The current evidence base for TH options for social communication intervention post-TBI is scarce, yet findings of initial studies are promising. Given the potential of TH to expand the variety and reach of neurorehabilitation services, and the current global shift towards virtual functioning, further such research appears warranted.